Policy : from ideas to implementation : in honour of Professor G. Bruce Doern - Doern, G. Bruce; Pal, Leslie A., 1954-; Prince, Michael J.; Toner, Glen B. (Published for the Carleton School of Public Policy and Administration by McGill-Queen's University Press, 2010)
Illuminating the ways in which neoliberal policies - such as the deregulation of economies and the transfer of governmental responsibilities to the private sector - have been implemented on a global scale, this book shows how neoliberalism has seeped into our social and political fabric and affected our daily lives.